6K2-induced vesicles can move cell to cell during turnip mosaic virus infection - Grangeon, Romain; Jiang, Jun; Wan, Juan; Agbeci, Maxime; Zheng, Huanquan; Laliberté, Jean-François (Frontiers in Microbiology, 2013)
To successfully infect plants, viruses replicate in an initially infected cell and then move to neighboring cells through plasmodesmata (PDs). However, the nature of the viral entity that crosses over the cell barrier into non-infected ones is not clear. The membrane-associated 6K2 protein of turnip mosaic virus (TuMV) induces the formation of vesicles involved in the replication and intracellular movement of viral RNA. This study shows that 6K2-induced vesicles trafficked towards the plasma membrane and were associated with plasmodesmata (PD). We demonstrated also that 6K2 moved cell-to-cell into adjoining cells when plants were infected with TuMV. 6K2 was then fused to photo-activable GFP (6K2:PAGFP) to visualize how 6K2 move intercellularly during TuMV infection. After activation, 6K2:PAGFP-tagged vesicles moved to the cell periphery and across the cell wall into adjacent cells. These vesicles were shown to contain the viral RNA-dependent RNA polymerase and viral RNA. Symplasmic movement of TuMV may thus be achieved in the form of a membrane-associated viral RNA complex induced by 6K2.